COMMUNICATION RELATIONSHIP OF HEALTH WORKERS TOWARDS THE IMPLEMENTATION OF BASIC IMMUNIZATION IN THE WORKING AREA OF BLANG KUTA HEALTH CENTER, BANDAR DUA DISTRICT, PIDIE JAYA REGENCY - Munawir, Munawir; Ichwansyah, Fahmi; Azwar, Eddy (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Basic immunization coverage in Pidie Jaya Regency from January to December was 29.6% for measles immunization. One of the health centers with the lowest basic immunization is Blang Kuta at 12.9%. This research aims to determine the relationship between health worker communication and the implementation of basic immunization in the work area of the Blang Kuta Health Center. Methods: This research is descriptive- analytic with a cross-sectional design. The population in this study was 145 mothers who had babies aged 0-12 years in the Blang Kuta Community Health Center working area. The sample, consisted of 60 respondents who were determined using the Proportional Random Sampling technique. Data analysis used the Chi-Square test with SPSS. Results: Based on univariate analysis shows that the implementation of basic immunization in the Kuta Blang Health Center working area is still low (61.7%), there is a lack of information sources (71.7%), there is a lack of media (76.7%), there is a lack of communication messages (73.3%), lack of recipients of information (58.3%). Based on bivariate analysis, there is a relationship between information sources (p value=0.012), communication messages (p value=0.043), and recipients of information (p value=0.015) on the implementation of basic immunization in the Blang Kuta Community Health Center Working Area in 2019. Recommendation: Health workers should improve their effective communication skills, so they can provide good and clear information about immunization procedures to the public, especially mothers who have babies and toddlers.